PENGEMBANGAN FLASHCARD DENGAN MENGGUNAKAN MODEL PBL UNTUK MENINGKATKAN ADVERSITY QUATIENT SISWA KELAS IV SISWA KELAS IV SDN KABUPATEN BLITAR - Hazin Tri Wulandari; Shofi Nur Amalia; Ragil Tri Oktaviani (Global Action and Education for Society, 2026)
This study aims to develop flash card learning media on the material of flat area with Problem Based Learning (PBL) approach to improve Adversity Quotient (AQ) of fourth grade students of SDN Ngoran 02 Blitar Regency. The background of this study is the low fighting power of students in learning mathematics which is characterized by passivity and giving up easily when facing difficult problems. The method used is Research and Development (R&D) with the ADDIE development model which includes the stages of analysis, design, development, implementation, and evaluation. Media expert validation scored 90% (very valid), material expert validation 95.5% (very valid), and feasibility validation 91.1% (very feasible). AQ measurement was conducted through pretest and posttest questionnaires, with an average pretest score of 6.06 and posttest of 10.18 from a maximum score of 12. These results show a significant increase in students’ AQ after the application of PBL-based flash card media. Thus, the flash card media developed is effective in increasing students’ fighting power in learning mathematics flat area material.